Condiciones higiénico sanitarias y percepción del consumidor durante la manipulación de alimentos en puestos de ventas de comidas Iquitos 2023 - Guerra Cubides, Coraima (2024)
The purpose of this study was to determine the relationship between hygienic and sanitary conditions and consumer perception during food handling in public street food stalls, San Juan Bautista district, Iquitos 2023. It is a quantitative, non-experimental, descriptive, cross-sectional and correlational study; The population consisted of 50 food stall handlers and 50 consumers. Observation and survey were used as techniques; and instruments, a checklist and Likert scale (validity 84.0% and 92.0%) and (reliability 82.1% and 81.1%). The results obtained were: age (mean 39.6±7.4 years); time in activity (average 3.4±0.8 years); 90.0% females and 10.0% males; 52.0% secondary education, 46.0% primary education, and 2.0% higher technical level; 28.0% with a handler's license and 72.0% without a license. Likewise, 48.0% of food stalls were in fair hygienic and sanitary conditions, 28.0% deficient, 16.0% good and 8.0% unacceptable; Regarding the consumer's perception of hygiene at the stalls, 86.0% rated it as good and 14.0% as very good. In conclusion, there is no significant difference between hygienic and sanitary conditions and the consumer's perception of hygiene in the stalls (value of p=0.201; > 0.05).